2018
DOI: 10.3390/jcdd5010003
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Eclampsia and Eclampsia: An Update on the Pharmacological Treatment Applied in Portugal

Abstract: Pre-eclampsia and eclampsia are two hypertensive disorders of pregnancy, considered major causes of maternal and perinatal death worldwide. Pre-eclampsia is a multisystemic disease characterized by the development of hypertension after 20 weeks of gestation, with the presence of proteinuria or, in its absence, of signs or symptoms indicative of target organ injury. Eclampsia represents the consequence of brain injuries caused by pre-eclampsia. The correct diagnosis and classification of the disease are essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
17

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 64 publications
1
60
0
17
Order By: Relevance
“…The ACOG revised guidelines define preeclampsia as a de-novo and abrupt onset persistent hypertension associated with proteinuria or pathological edema or thrombocytopenia or impaired liver or kidney function or new onset of cerebral or visual disturbances (1,5). Eclampsia is defined as preeclampsia with sudden development of seizures or coma during the gestational or postpartum period, non-attributable to other neurological diseases that justify the convulsive state (6). Globally, preeclampsia is a leading cause of maternal and infant illness and mortality claiming up to 76,000 maternal and 500,000 infant deaths per year, according to conservative estimates (7).…”
Section: Introductionmentioning
confidence: 99%
“…The ACOG revised guidelines define preeclampsia as a de-novo and abrupt onset persistent hypertension associated with proteinuria or pathological edema or thrombocytopenia or impaired liver or kidney function or new onset of cerebral or visual disturbances (1,5). Eclampsia is defined as preeclampsia with sudden development of seizures or coma during the gestational or postpartum period, non-attributable to other neurological diseases that justify the convulsive state (6). Globally, preeclampsia is a leading cause of maternal and infant illness and mortality claiming up to 76,000 maternal and 500,000 infant deaths per year, according to conservative estimates (7).…”
Section: Introductionmentioning
confidence: 99%
“…Further, a study by Purnima and Sonal and another study by Munde et al also concludes that LDH and GGT can be effectively used as biochemical markers as it reflects the severity of preeclampsia and maybe helpful in its management [31,32]. Neha V Bhave further claims that LDH effectively predicts maternal and perinatal outcomes along with the severity of the disease [17].…”
Section: Discussionmentioning
confidence: 96%
“…Hypertensive disorders of pregnancy, characterized by heterogenous clinical and laboratory manifestations and varied pathogenesis, are one of the leading causes of maternal and neonatal morbidity and mortality [17,18]. In the era of laboratory guided diagnosis, laboratory assessment is gaining momentum in evaluation of HDPs.…”
Section: Discussionmentioning
confidence: 99%
“…1| Jan -Apr 2019 eclampsia, where procedures and surgery are performed as indicated by severe preeclampsia. 8,9 Previous research on preeclampsia showed low placental energy status either due to impaired glycolysis, ischemia caused by decreased maternal placental blood flow, or both, and is responsible for fetal growth restriction. 10 The presence of these abnormalities causes significant metabolic abnormalities in the placenta of pregnant women who experience severe preeclampsia and are thought to contribute to disturbances of other metabolic functions, including metabolic functions of blood glucose, lipid, and protein.…”
Section: Original Articlementioning
confidence: 99%